Public Employment Offices in the United States and Germany - Bogart, E. L. (Quarterly Journal of Economics, 1900)
E. L. Bogart; Public Employment Offices in the United States and Germany, The Quarterly Journal of Economics, Volume 14, Issue 3, 1 May 1900, Pages 341–377, htt